1996
DOI: 10.1073/pnas.93.1.456
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of mitomycin C and porfiromycin to aerobic and hypoxic Chinese hamster ovary cells overexpressing human NADPH:cytochrome c (P-450) reductase.

Abstract: Purified NADPH:cytochrome c (P-450) reductase (FPT; NADPH-ferrihemoprotein oxidoreductase, EC (for appropriate references, see refs. 9-11). Evidence exists to suggest that alkylation of DNA is the critical lesion in the cytotoxicity of the mitomycins to both hypoxic and oxygenated cells (12, 13).Studies in mice bearing transplanted solid tumors demonstrated the ability of these antibiotics to reach and kill hypoxic cells and, in combination with x-irradiation, to produce additive or greater than additive cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
45
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
7
45
2
Order By: Relevance
“…MC at 2.5, 5.0, 10, 12.5, and 15 M was then introduced into the cultures using a Hamilton syringe without compromising the hypoxic environment, and cultures were incubated for 1 h. Cells under aerobic conditions were treated identically but gassed with a humidified atmosphere of 95% air plus 5% CO 2 . MC-treated cells were then washed, harvested by trypsinization, and assayed for survival using a clonogenic assay (27). Macroscopic colonies consisting of more than 40 cells were counted, and the plating efficiencies, defined as the number of macroscopic colonies counted divided by the number of cells plated, was determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC at 2.5, 5.0, 10, 12.5, and 15 M was then introduced into the cultures using a Hamilton syringe without compromising the hypoxic environment, and cultures were incubated for 1 h. Cells under aerobic conditions were treated identically but gassed with a humidified atmosphere of 95% air plus 5% CO 2 . MC-treated cells were then washed, harvested by trypsinization, and assayed for survival using a clonogenic assay (27). Macroscopic colonies consisting of more than 40 cells were counted, and the plating efficiencies, defined as the number of macroscopic colonies counted divided by the number of cells plated, was determined.…”
Section: Methodsmentioning
confidence: 99%
“…This separation, known as the "aerobic/hypoxic differential," is reflected in the cytotoxicity profiles for Chinese hamster ovary (CHO) cell transfectants overexpressing NPR (27) and NBR (28,29) but not for those overexpressing NQO1 (30). Thus, although NPR and NBR are not important enzymes in the activation of MC under aerobic conditions, they contribute to the preferential activation of MC in hypoxia.…”
mentioning
confidence: 99%
“…E09 activity appears to be particularly sensitive to the level of DT-diaphorase under oxygenated conditions (Plumb et al, 1994). Increasing DTdiaphorase activity in gastric carcinoma (Mikami et al, 1996) or Chinese hamster ovary cells (Belcourt et al, 1996), by transfection of the NQO, gene, increased the sensitivity of the cells to MMC. In contrast, transfection of the NQO, gene into NIH 3T3 mouse fibroblasts did not increase MMC activity in these cells .…”
mentioning
confidence: 99%
“…In contrast, transfection of the NQO, gene into NIH 3T3 mouse fibroblasts did not increase MMC activity in these cells . In addition, DT-diaphorase did not appear to play a major role in activation of MMC in some cell lines in vivo (Nishiyama et al, 1993) or under hypoxia (Begleiter et al, 1992;Belcourt et al, 1996). Furthermore, DT-diaphorase did not effect the toxicity of the benzotriazine di-N-oxide, tirapazamine (Patterson et al, 1994) and protected cells from the toxicity of the quinone agents, menadione (Atallah et al, 1988), hydrolysed benzoquinone mustard, benzoquinone mustard and benzoquinone dimustard (Begleiter and Leith, 1990).…”
mentioning
confidence: 99%
“…Cell lines with high levels of DT-diaphorase are more sensitive to MMC (Begleiter et al, 1989;Ross et al, 1993;Mikami et al, 1996), and studies have shown a good correlation between the level of DT-diaphorase activity and the sensitivity to MMC in human tumour cell lines (Fitzsimmons et al, 1996). Transfecting the NQO1 gene into Chinese hamster ovary cells (Belcourt et al, 1996) and gastric carcinoma (Mikami et al, 1996) increased MMC cytotoxic activity to the cells.…”
mentioning
confidence: 99%